ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ENGAGEMENT TENAGA PENDIDIK PADA PROGRAM STUDI MANAJEMEN PEMASARAN POLITEKNIK NEGERI JAKARTA - Anita Rahmawati (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
In the last few decades, many well-known companies and business media have discussed the topic of employee engagement. Employee engagement has a major effect on employee performance in a company or institution. The topic of engagement is still rarely found in the realm of education. In the realm of education, in this case universities, educators are an important element as one of the determinants of ensuring the success of an educational process. This study was conducted to analyze the factors that influence simultaneously and or partially on the engagement of educators (lecturers) in the Study Program of Marketing Management in Jakarta State Polytechnic. The factors used in this research are leadership, work environment, compensation, training, and teamwork. The method used is quantitative research conducted by distributing valid questionnaires to 21 educators of the Study Program of Marketing Management. The data analysis method used is descriptive analysis and multiple linear regression analysis with SPSS software version 25.0 test tool. The results showed that only teamwork variable had a significant effect on the engagement of educators. Meanwhile, the variables of leadership, training, work environment, compensation, and teamwork simultaneously have a positive and significant effect on the engagement of educators